Lower-middle Viséan transgressive carbonates in Morocco: Palaeobiogeographic insights. (August 2020) - Cózar, Pedro; Vachard, Daniel; Izart, Alain; Said, Ismael; Somerville, Ian; Rodríguez, Sergio; Coronado, Ismael; El Houicha, Mohamed; Ouarhache, Driss
Abstract: Foraminifera have been used to revise the biostratigraphy of all known Mississippian outcrops in Morocco cited either as early Viséan (or its equivalent V2a or V2a/b chronozones or the regional Cfm1 biozones), or mid Viséan (or the foraminiferal zones V2b-V3a or Cfm 2-Cfm 3 biozones). This group of microfossils occur in shallow-water limestones within siliciclastic-dominant successions. Most of the previously determined lower Viséan ages for the outcrops are now interpreted either as middle or even late Viséan. Similarly, some outcrops originally assigned to the mid Viséan are now considered as late Viséan. Only two successions can be confirmed as belonging to the early Viséan in the Western Meseta. The first succession, of uppermost lower Viséan age (Cf4γ-δ subzones or MFZ11 zone), occurs in the lower part of the Sidi Sebaa Formation in the Mdakra Massif (south of the Sidi Bettache Basin). The second succession occurs in a small area in the lower part of the Khenifra Nappe (in the so-called Hvs1' Formation), which is assigned to the base of the Viséan (Cf4α2 subzone or MFZ9 zone). Middle Viséan outcrops are more common, occurring in the western part of the Western Meseta (Mdakra and Khatouat massifs), north-central Western Meseta (Tilouine, Bouqachmir, El Goulib, Jbel Bouechchot), as well as in the South Western Meseta (Haouz-High Atlas of Marrakech) and the central High Atlas (Skoura). In contrast, the Viséan succession in the Anti-Atlas domain is more continuous, from early to mid Viséan. This scarcity of lower Viséan outcrops suggests that the Moroccan Meseta was mostly an uplifted region at that time. The recognition of the early Viséan in the Mdakra Massif suggests a marine connection from the west or northwest, linked with the Rheic Ocean, with an opposite orientation (from the southeast) for the main transgressions in the Meseta in the late Viséan. Taking into consideration previous tectonic reconstructions of Morocco, the presence of early Viséan marine rocks in the Khenifra region can only be explained by a southward connection with the Sahara across the Tinerhir and Tafilalt regions linking with the Palaeotethys Ocean, which later covered areas within the High Atlas during the mid Viséan. This connection during the early Viséan, suggests a relatively close position between the Moroccan Meseta and Gondwana, in spite of the disparity in the lithological successions; this is also recognized in the mid Viséan. Thus, it appears that the Moroccan Meseta had not yet achieved its final emplacement completely juxtaposed to Gondwana. Graphical abstract: Image 1 Highlights: The entire early and mid Viséan of Morocco is revised. Early Viséan is a period of predominant emergent lands. Lower Viséan Moroccan Meseta was poorly connected to the Rheic Ocean and Palaeotethys. Mid Viséan Morocco connected Rheic Ocean and Palaeotethys.